Pengembangan Media Pembelajaran Flip Book Berbasis Augmented Reality untuk Meningkatkan Hasil Belajar IPAS Materi Makan dan Dimakan - Sabrina Idamatus Silmi; Kurniana Bektiningsih (Postgraduate, University of Mataram, 2025)
This study aims to develop and evaluate the effectiveness of Augmented Reality (AR)-based Flip Book as learning media to improve students' understanding of food chain material in Elementary School Natural and Social Sciences (IPA-SD) subjects for grade V students of SDN 1 Munggu. This research uses a Research and Development (R&D) approach that adapts the Borg and Gall model with eight stages, namely needs analysis, product design, expert validation, product revision, product trials, and field trials, namely with pretest and posttest data. This AR-based flipbook obtained a media validation assessment of 93.75% with a very feasible category and material validation which obtained 88.75% with a very feasible category. Data collection using pre-test and post-test was carried out in two groups, namely large groups (N = 20) and small groups (N = 8). The results showed a significant increase in student learning outcomes, as indicated by statistical analysis that showed a significant difference between pre-test and post-test scores (p < 0.05). The N-Gain (Normalized Gain) value criteria for measuring learning effectiveness are generally categorized as low (<0.3), medium (0.3 ≤ N-Gain ≤ 0.7), and high (>0.7). In this media development, an N-gain of 0.38 was obtained which is included in the medium criteria, this indicates that the AR-based Flip Book is effective in increasing understanding, but further development is needed to get the optimal impact.